Analisis Perawatan Untuk Mendeteksi Risiko Kegagalan Komponen Pada Excavator 390D - Armin Darmawan; Amrin Rapi; Syafrillah Ali (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2016)
This study is concerned with maintenance on a heavy equipment excavator 390D series HE4019, one of the main tools used to support the process of nickel production. Major constraint in using this tool is an insufficiently planned maintenance such that the tool affected operational and production process of nickel. Failure mode and effect analysis (FMEA) method is used to identify the risks of failure of critical components on the performance of the unit. Based on risk priority number (RPN), three critical components are found as leading causes of unit downtime. These are stick cylinder (RPN 288), fuel filter (RPN 280) and oil pan (RPN 240), respectively. Mean time between failure (MTBF) scores of stick cylinder, fuel filter and oil pan are 1,288.91 hours, 334.04 hours and 1,455.77 hours, respectively. Each of making rod of the cylinder covered, periodically flushing the fuel tank and taking on a warning sign on the couplers and coating the gasket with an additional layer during installation, in the meantime, are proposed as preventive maintenance for each the three critical components.